Bilateral arterial thoracic outlet syndrome with intermittent subclavian artery occlusion. (April 2011) - Lotun, Kapildeo; Soukas, Peter A; Bueno, Ralph; Igbokidi, Oyidie; Owens, Christopher; Schainfeld, Robert M
Arterial thoracic outlet syndrome presentation is frequently misdiagnosed because of its varied clinical presentation. We present a case of a young female who presented with right upper extremity Raynaud''s phenomenon. She was ultimately referred for a vascular medicine consultation after inability to palpate the radial pulse by the neurologist. She was diagnosed with arterial thoracic outlet syndrome, secondary to a congenital cervical rib, which was contributing to intermittent subclavian artery occlusion. She underwent cervical and first rib resection and returned 6 months later with symptoms in the left upper extremity. Her clinical presentation, diagnosis and therapeutic options are discussed in this article along with a review of the literature.